PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN BERBASIS FRAUD TRIANGLE MELALUI KUALITAS AUDIT SEBAGAI PEMODERASI - Devi Sintabela; Achmad Badjuri (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This study aims to determine the effect of financial stability, external pressure,ineffective supervision, and rationalization as independent variables from the fraudtriangle on fraudulent financial reporting with moderated audit quality. Thisresearch uses banking company objects listed on the Indonesia Stock Exchange in2019-2021. The sample selection used purposive sampling by producing 75samples. The results show that only financial stability has a negative effect onfraudulent financial statements proxied by earnings management. External pressurevariables, ineffective supervision, and rationalization have no effect on fraudulentfinancial reporting. Audit quality as a moderating variable is unable to moderatethe effect of all independent variables on fraudulent financial statements.